Optical properties of materials and their applications - Jai, Singh (Wiley series in materials for electronic and optoelectronic applications, 2020)
"Optical properties of a material change or affect the characteristics of light passing through it by modifying its propagation vector or intensity. Two of the most important optical properties are the refractive index n and the extinction coefficient K, which are generically called optical constants; though some authors include other optical coefficients within this terminology. The latter is related to the attenuation or absorption coefficient . In Part I, in this chapter, we present the complex refractive index, the frequency or wavelength dependence of n and K, so-called dispersion relations, how n and K are inter-related, and how n and K can be determined by studying the transmission as a function of wavelength through a thin film of the material"--